Truthfully Misleading: Truth, Informativity, and Manipulation in Linguistic Communication - Reboul, Anne (Frontiers in Communication, 2021)
Linguistic communication is geared toward the exchange of information, i.e., changing the addressee’s world views. In other words, persuasion is the goal of speakers and the force of the speaker’s commitment as indicated in the utterance is an important factor in persuasion. Other things being equal, the stronger the speaker’s commitment, the easier the persuasion. However, if deception is detected, the stronger the speaker’s commitment, the harsher the punishment, i.e., the damage to his or her reputation. One way for cheaters to avoid detection and/or to mitigate punishment is to downplay their commitment to what they mean through the utterance by making its content less informative, i.e., by producing underinformative utterances. Underinformativity is also a powerful way of triggering context-dependent and inference-based interpretation that goes beyond what is said. This allows speakers to indirectly communicate false content while producing an utterance that is literally true. This phenomenon of truthfully misleading is the topic of the present paper. As will be seen, it allows speakers to leave part of the responsibility for the false content to their hearers, with the double effect that they can claim to have been misunderstood (plausible denial), that what they said was literally true and to explain the underinformativity of the utterance through ignorance.